2005
DOI: 10.1093/brain/awh446
|View full text |Cite
|
Sign up to set email alerts
|

Cortical triggers in generalized reflex seizures and epilepsies

Abstract: Activation of specific cortical territories by sensory stimuli or of less restricted areas of the brain by cognitive stimuli is known to induce apparently generalized seizures in predisposed patients; this is clinically and electroencephalographically distinct from reflex triggering of partial seizures. Photosensitive patients may have seizures when exposed to environmental stimuli producing appropriate flickering light or geometric patterns. Some children with benign myoclonic epilepsy in infancy have seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 97 publications
4
115
0
5
Order By: Relevance
“…[1][2][3][4] The relation between spontaneous epileptiform activity and cognitive functions has been studied with an increasing interest since present. [7][8][9][10][11][12][13][14] Seizures induced by higher mental activities have encouraged studies which were designed with special EEG activation methods to show any effect of mental tasks on the EEG of epileptic patients. [11][12][13][14] Matsuoka et al [11] used a neuropsychological method testing for various mental activities as a part of routine EEG examination for patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The relation between spontaneous epileptiform activity and cognitive functions has been studied with an increasing interest since present. [7][8][9][10][11][12][13][14] Seizures induced by higher mental activities have encouraged studies which were designed with special EEG activation methods to show any effect of mental tasks on the EEG of epileptic patients. [11][12][13][14] Matsuoka et al [11] used a neuropsychological method testing for various mental activities as a part of routine EEG examination for patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] It has been also demonstrated that spesific or nonspecific complex cognitive activities such as calculations, constructive activities, drawing, playing strategic board games are able to precipitate seizures. [7][8][9][10][11][12][13][14][15] In the treatment of JME not only antiepileptic drug therapy but also identification and regulation of seizure precipitant factors are important.…”
Section: Introductionmentioning
confidence: 99%
“…Refleks epilepsilerin oluşum mekanizması halen net anlaşılama-mıştır.Ancak nöbeti tetikleyen uyarana karşı beyin kortkesinin aşırı duyarlı olduğu düşünülmektedir (8). Chauvel ve ark.…”
Section: Discussionunclassified
“…Long-range connections were increased during SWD, particularly between frontal and posterior brain regions. In a fMRI study involving a working memory paradigm [50], the researchers found increased functional connectivity between the motor system and areas of higher cognitive functions within the frontal and the parietal lobes, which might explained clinical feature that myoclonic jerks could be triggered by cognitive effort in some patients with JME [51]. Additionally, in patients under valproic acid (VPA) treatment, abnormal motor cortex co-activation was negatively associated with an increasing daily VPA dose, which might underlie the beneficial effect of VPA on controlling myoclonic jerks [50].…”
Section: Reviewmentioning
confidence: 99%